Multi-challenge aspects in fatigue due to the combined occurrence of multiaxiality, variable amplitude loading, and size effects - M. Vormwald (Fracture and Structural Integrity)
The three major issues which contribute to uncertainties in fatigue life estimations are the limited transferability of material data obtained in a laboratory for describing the fatigue behavior of components, the lack of damage accumulation rules to realistically take into account the effects of various load sequences, and the uncertainty in the assessment of multiaxial stress states. The three issues contribute to life prediction errors in a balanced way. Some modeling effort was spent in joining solution proposals in a unifying short crack model. The actual state is presented in the paper together with some ideas for further improvement as well as simplification for promoting the model’s acceptance in practical applications.